Acquired von Willebrand Syndrome in left Impella supported cardiogenic shock patients. (25th November 2020) - Vandenbriele, C; Balthazar, T; Engelen, M; Adriaenssens, T; Verhamme, P; Peerlinck, K; Janssens, S; Jacquemin, M
Abstract: Background: Bleeding is a main cause of morbidity and mortality in critically ill cardiogenic shock patients, supported by short-term percutaneous mechanical circulatory support (pMCS) devices. Bleeding not only occurs because of obligatory heparin and antiplatelet therapy (both required in the prevention of pump and stent thrombosis) but possibly also results from device-related coagulopathy. Similar to long-term ventricular assist devices, mechanical shear-induced acquired von Willebrand syndrome (AVWS) might further increase the bleeding risk. Therefore, we aimed to investigate the effect of left Impella percutaneous continuous flow pumps on the development of AVWS due to shear-induced excessive cleavage of large vWF multimers by the metalloproteinase ADAMTS-13, resulting in loss of high-molecular-weight vWF multimers. Methods: Between March 2019 and January 2020, all cardiogenic shock patients supported by a left Impella and referred to a single tertiary ICU were studied. Both vWF Antigen (vWF:Ag) and vWF:GPIbR (ristocetin-induced binding of vWF to a recombinant wildtype Glycoprotein Ib fragment) levels were measured by chemiluminescent immunoassays using an AcuStar (Werfen) assay to determine the vWF:GPIbR /vWF:Ag ratio (normal range ≥1.0). VWF multimer analysis was performed by electrophoresis. On-pump analyses were performed 12h after implantation and off-pump analyses 12h after Impella explantation. Patients who died on-pump were excluded because of lack of paired data after explantation. Results: Eight left Impella patients (four Impella CP, four Impella 5.0) were analyzed for AVWS. The vWF:GPIbR /vWF:Ag ratio was <1.0 in all patients on-pump (mean±SD 0.68±0.1 versus 1.1±0.15 off-pump (panel A; p=0.0018)) and thus AVWS was detected in all Impella-supported patients. The presence of AVSW was also confirmed by loss of large vWF multimers on-pump (panel B). Four patients (50%) had mucosal bleeds (epistaxis or gastrointestinal), none of them requiring transfusion. The mean rise in ratio 12h after pump removal was 0.35 which was also reflected by recovery of large multimers by electrophoresis (panel B). Conclusions: Our data highlight the rapid onset and reversal of AVWS in all studied cardiogenic shock patients, supported by a left Impella pump. The determination of the GPIbR /vWF:Ag ratio with the AcuStar appears a reliable and faster test to detect AVWS as compared to vWF multimers electrophoresis. Further research into innovative pharmacological interventions (e.g. ADAMTS-13 inhibitors) should target pMCS-induced AVWS in an effort to reduce hemostatic complications in this critically ill ICU population. Funding Acknowledgement: Type of funding source: None